COVID-19 Vaccines in Indonesia: Knowledge, Attitudes, and Acceptance Among Dental Professionals - Theodorea, Citra Fragrantia; Widyarman, Armelia Sari; Dewanto, Iwan; Astoeti, Tri Erri (Frontiers in Medicine, 2021)
Background: At the time of writing, the number of Coronavirus Disease 2019 (COVID-19) cases in Indonesia has exceeded 4 million. Many dental professionals in Indonesia have been exposed to the virus through close contact with aerosols and droplets from the oral cavities of their patients and have subsequently become infected. It is necessary to achieve high COVID-19 vaccination coverage rates among health workers. However, immunizations are voluntary, and some healthcare workers may be reluctant to receive them. The aim of this study was to evaluate the knowledge, attitudes, and acceptance of dental professionals of COVID-19 vaccines. Materials and methods: A cross-sectional study was conducted among dentists taking part in the Indonesia Dental Association webinar in June 2021. The questionnaire consisted of 15 questions developed after being reviewed by experts. The questionnaire collected demographic data and data on the dental professionals’ knowledge and acceptance of COVID-19 vaccines in Indonesia as well as their attitudes toward COVID-19 vaccines. The data were analyzed using descriptive statistics and expressed as frequencies and percentages. A chi-square test was used to investigate the association between professional activity and acceptance of COVID-19 vaccines. Results: In total, 779 dentists from 34 provinces in Indonesia completed the questionnaire. There were 646 (83%) females and 133 (17%) males, with an age range of 24–73 years. In terms of the distribution of professional affiliations, the respondents included 23 (3%) academics, 285 (36.5%) private hospital/private practice practitioners, and 471 (60.5%) national hospital practitioners. In the statistical analysis, unadjusted odds ratios (ORs) were calculated with their 95% confidence intervals (CIs). Conclusions: Acceptance of COVID-19 vaccines is an essential determinant of vaccine uptake and the likelihood of controlling the COVID-19 pandemic. There is an agreement between dental professionals in private hospitals and academic faculties (dental schools) regarding the need for COVID-19 vaccination. Developing strategies to reduce public hesitation and increase trust is vital for implementing vaccination programs, and dentists can play a role in increasing the uptake of COVID-19 vaccines.